2013
DOI: 10.1213/ane.0b013e31828f29f8
|View full text |Cite
|
Sign up to set email alerts
|

Hypobaric Spinal Anesthesia with Ropivacaine Plus Sufentanil for Traumatic Femoral Neck Surgery in the Elderly

Abstract: The effective dose of hypobaric ropivacaine combined with sufentanil 5 µg providing 95% success in spinal anesthesia for traumatic femoral neck surgery in the elderly is ED95 = 9 mg (95% confidence interval, 8-14). Using doses exceeding the ED95 may increase the incidence of hypotension. If doses less than the ED95 are chosen, the use of additional analgesia may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Sufentanil is a type of narcotic drug and opioid receptor agonist, and contains citrate as the main pharmacological component ( 2 4 ). Sufentanil is easily transferred through the blood-brain barrier with its high lipid solubility, and can bind with plasma protein for a good analgesic effect, with a longer interval for anesthesia ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufentanil is a type of narcotic drug and opioid receptor agonist, and contains citrate as the main pharmacological component ( 2 4 ). Sufentanil is easily transferred through the blood-brain barrier with its high lipid solubility, and can bind with plasma protein for a good analgesic effect, with a longer interval for anesthesia ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, laparoscopic radical resection is the most widely used clinical treatment for colorectal cancer, however, it causes great discomfort for the patient ( 2 ). To improve the quality of anesthesia in the laparoscopic radical resection of colorectal cancer is a challenge for the medical field ( 3 , 4 ). Target-controlled infusion (TCI) is a new approach of anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study demonstrated that a dermatome level up to T12 may satisfy the requirement of surgical anesthesia for hip replacement [21]. The nerves innervating the hip joints derived from the ventral rami of the spinal nerve roots of the lower part of the lumbar plexus (L2-4) and the upper part of the sacral plexus (L4-S1) [22].…”
Section: Discussionmentioning
confidence: 99%
“…1 The reduction of local anesthetic dose (adding adjuvants like opioids) and sympathectomy can contribute to more favourable haemodynamics and theoretically better outcomes in the elderly population. 16,17 We prefer to use hypobaric spinal anesthesia, due to difficulties of changing patient positions, advantage of decrease in urinary retention and better patient and surgeon satisfaction. During hypobaric spinal anesthesia, hypotension incidence is reduced, and recovery period shortened in our study.…”
Section: Concentration and Baricitymentioning
confidence: 99%